Conductive resin composition
Patent Information
- Application Number
- JP2021086318
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-26
- Filing Date
- 2021-05-21
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-05-21
AI Technical Summary
【0009】 本発明は、導電膜を形成した際の体積抵抗率が低く、良好な導電性を示すものであり、各種基材に対する密着性が良好であり、保存安定性に優れ、導電性インクや回路接続材料等として有用な導電性樹脂組成物が得られるという顕著な効果を発揮する。 さらに、本発明の導電性樹脂組成物は、導電接続を形成する際の加熱温度を低くすることができるため、従来基材として使用されていなかった低融点のプラスチックを基材として用いることが可能となる。 本発明の導電性樹脂組成物は、プリンテッドエレクトロニクス材料として有用であり、表示装置、車両関連部品、IoT、移動通信システム(Mobile Communication System)等の各種電子機器等の大量生産に際して極めて有用である。
Smart Images

Figure 0007639249000001 
Figure 0007639249000002 
Figure 0007639249000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive resin composition. The present invention also relates to a conductive ink used for forming a circuit or the like by screen printing on a substrate, and a circuit connecting material used for conductively connecting an electronic component to a circuit board or the like. [Background technology]
[0002] A wide variety of conductive resin compositions are known, and are used as conductive pastes, conductive inks, conductive paints, circuit connecting materials, conductive adhesives, etc. for various applications such as the formation of electronic circuits and the adhesion of electronic components. For example, there is a need for conductive inks that are adaptable to a variety of printing methods and that are useful in the manufacture of flexible plastic substrates and the like having conductive structures, such as interconnects, traces, electrodes, and the like. For example, in electronic devices such as computers and mobile phones, there is a demand for circuit connection materials that enable high-density mounting and high integration of various electronic components such as LED elements, semiconductor elements, and capacitors on the same circuit board.
[0003] However, conventional conductive resin compositions have low adhesion to substrates and often do not provide sufficient adhesive strength when bonding electronic components and circuits, resulting in low reliability of conductive connections. Furthermore, the dispersibility of the conductive powder and the solder powder in the conductive resin composition may become insufficient, leading to an increase in the volume resistivity of the film of the conductive resin composition and therefore to insufficient conductivity. For this reason, there is a demand for conductive resin compositions that suppress the occurrence of short-circuit failures and provide highly reliable conductive connections for electronic devices in which the spacing between wiring patterns is narrowed due to miniaturization of parts and high circuit density.
[0004] In response to such needs, Patent Documents 1 to 3 disclose conductive resin compositions containing a conductive powder, a solder powder, and a resin component. However, these conductive resin compositions have one or more areas that need improvement in terms of adhesion to plastic substrates or glass, electrical conductivity, and storage stability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-305588 A [Patent Document 2] JP 2011-23574 A [Patent Document 3] Japanese Patent Application Publication No. 64-59786 Summary of the Invention [Problem to be solved by the invention]
[0006] Until now, no conductive resin composition has been known that has sufficient adhesion to plastic substrates and glass, sufficient conductivity when formed into a film, excellent storage stability, and does not contain lead components that have adverse effects on the human body and the environment.
[0007] The problem to be solved by the present invention is to provide a conductive resin composition which, when a conductive film is formed, has low volume resistivity, exhibits good electrical conductivity, has good adhesion to various substrates, and has excellent storage stability, and is useful as a conductive ink, a circuit connecting material, etc. [Means for solving the problem]
[0008] Means for Solving the Problems The present inventors have conducted extensive research to find that the above problems can be solved by using a conductive resin composition having a specific composition, and have thus completed the present invention. Specifically, it is as follows: [1] One or more conductive powders selected from the group consisting of nickel-based metal powder, silver-based metal powder, copper-based metal powder, zinc-based metal powder, aluminum-based metal powder, iron-based metal powder, and gold-based metal powder; Lead-free solder powder, A polyvinyl butyral resin, An organic acid compound, A conductive resin composition comprising: [2] The volume resistivity of the conductive film is 1.0×10 -2 [1] An electrically conductive resin composition having a resistivity of less than Ω·cm. [3] A conductive ink comprising the conductive resin composition of [1] or [2]. [4] A circuit connecting material comprising the conductive resin composition of [1] or [2]. Effect of the Invention
[0009] The present invention exerts a remarkable effect in that a conductive resin composition can be obtained which, when a conductive film is formed, has low volume resistivity and good electrical conductivity, has good adhesion to various substrates, and has excellent storage stability, and is useful as a conductive ink, a circuit connecting material, etc. Furthermore, since the conductive resin composition of the present invention allows the heating temperature to be lowered when forming a conductive connection, it becomes possible to use low-melting point plastics, which have not been used as substrates in the past, as substrates. INDUSTRIAL APPLICABILITY The conductive resin composition of the present invention is useful as a printed electronics material, and is extremely useful in mass production of various electronic devices such as display devices, vehicle-related parts, IoT, and mobile communication systems. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention relates to a conductive resin composition, a conductive ink, and a circuit connecting material, which will be described in detail below.
[0011] [Conductive resin composition] <Conductive powder> The conductive powder, which is at least one type selected from the group consisting of nickel-based metal powder, silver-based metal powder, copper-based metal powder, zinc-based metal powder, aluminum-based metal powder, iron-based metal powder, and gold-based metal powder, is not particularly limited as long as it is a powder containing any of nickel, silver, copper, zinc, aluminum, iron, and gold as a metal component. Examples of the conductive powder include powder of the metal itself, alloy powder containing the metal, and coated powder at least a part of the surface of which is coated with the metal. The conductive powders may be used alone or in combination of two or more.
[0012] The shape of the conductive powder is not particularly limited. Spherical, nearly spherical (for example, with a length-to-width aspect ratio of 1.5 or less), flat, block-like, plate-like, polygonal pyramidal, polyhedral, flaky, rod-like, fibrous, needle-like, irregular, and other shapes can be used depending on the application. In the present invention, from the viewpoints of oxidation resistance, volume resistivity, dispersibility, handling, and the like, spherical, nearly spherical, flat, or flaky shapes are preferred.
[0013] The volume average particle size of the conductive powder is not particularly limited. D50 can be, for example, 0.5 μm or more, preferably 1.0 μm or more, more preferably 5.0 μm or more, and can be, for example, 50.0 μm or less, preferably 15.0 μm or less. When D50 is 0.5 μm or more, the oxidation resistance of the conductive powder is improved, and dispersibility and handling are improved. When D50 is 50.0 μm or less, the volume resistivity can be reduced, and dispersibility and handling are improved.
[0014] In the present invention, the conductive powder is preferably a nickel-based metal powder and / or a silver-based metal powder from the standpoint of conductivity, cost, and the like.
[0015] (Nickel-based metal powder) The nickel-based metal powder is not particularly limited as long as it is a powder containing metallic nickel, and examples thereof include metallic nickel powder, nickel alloy powder, and nickel-coated powder. The nickel-based metal powders can be used alone or in combination of two or more.
[0016] The metallic nickel powder is obtained by powdering metallic nickel. The content of nickel in the metallic nickel powder is not particularly limited. For example, it is 95% by mass or more, preferably 97% by mass or more, and more preferably 99% by mass or more.
[0017] The nickel alloy powder is not particularly limited as long as it is an alloy powder containing nickel. The nickel content in the nickel alloy powder can be appropriately determined from the viewpoint of the melting point of the nickel alloy powder and the reactivity with the lead-free solder powder. It is preferably 3 mass% or more, more preferably 5 mass% or more, and even more preferably 10 mass% or more, and is preferably less than 95 mass%. The nickel content in the nickel-containing powder can be easily measured using an X-ray fluorescence analysis (XRF) device or the like. Examples of nickel alloy powders include Ni-Fe based alloys (Ni-58Fe, etc.), Ni-Cu based alloys (Ni-75Cu, etc.), Ni-Cu-Zn based alloys (Ni-6Cu-20Zn, etc.), Ni-Cr based alloys, and Ni-Cr-Ag based alloys.
[0018] The nickel-coated powder has at least a portion of the particle surface coated with metallic nickel. Examples of particles that form the nickel-coated powder include one or more types selected from the group consisting of metal particles (e.g., Cu particles, Ag particles, Pd particles, alloy particles, etc.), organic polymer particles, inorganic particles such as glass and ceramic, mineral particles, etc. The metallic nickel coating may be performed by plating, vapor deposition, etc. The thickness of the metallic nickel coating is not particularly limited, but is preferably about 0.01 μm to 5 μm.
[0019] The nickel-based metal powder may further contain other atoms that are inevitably mixed in. Examples of such other atoms include one or more selected from the group consisting of Ag, Mn, Sb, Si, K, Na, Li, Ba, Sr, Ca, Mg, Be, Zn, Pb, Cd, Tl, V, Al, Zr, W, Mo, Ti, Co, Sn, and Au. The content of other atoms in the nickel-containing powder is, for example, 3% by mass or less, and preferably 1% by mass or less.
[0020] (Silver metal powder) The silver-based metal powder is not particularly limited as long as it is a powder containing metallic silver, and examples thereof include metallic silver powder, silver alloy powder, and silver-coated powder. The silver-based metal powders may be used alone or in combination of two or more.
[0021] The metallic silver powder is obtained by powdering metallic silver. The silver content in the metallic silver powder is not particularly limited. For example, it is 95% by mass or more, preferably 97% by mass or more, and more preferably 99% by mass or more.
[0022] The silver alloy powder is not particularly limited as long as it is an alloy powder containing silver. The silver content in the silver alloy powder can be appropriately determined from the viewpoint of the melting point of the silver alloy powder and the reactivity with the lead-free solder powder. It is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 10% by mass or more, and is preferably less than 99% by mass. The silver content in the silver-containing powder can be easily measured using an X-ray fluorescence analysis (XRF) device or the like. Examples of silver alloy powder include Ag-Cu based alloys, Ag-Pd based alloys, and Ag-Pt based alloys.
[0023] The silver-coated powder has at least a portion of the particle surface coated with metallic silver. Examples of particles that form the silver-coated powder include one or more types selected from the group consisting of metal particles (e.g., Cu particles, Pd particles, Al particles, alloy particles, etc.), organic polymer particles, inorganic particles such as glass and ceramic particles, mineral particles, etc. The metallic silver coating may be performed by plating, vapor deposition, etc. The thickness of the metallic silver coating is not particularly limited, but is preferably about 0.01 μm to 5 μm.
[0024] The silver-based metal powder may further contain other atoms that are inevitably mixed in. Examples of such other atoms include one or more selected from the group consisting of Mn, Sb, Si, K, Na, Li, Ba, Sr, Ca, Mg, Be, Zn, Pb, Cd, Tl, V, Al, Zr, W, Mo, Ti, Co, Sn, Cu, Ni, Au, etc. The content of other atoms in the silver-containing powder is, for example, 3% by mass or less, and preferably 1% by mass or less.
[0025] (Content) The content of the conductive powder in the conductive resin composition is not particularly limited. It can be appropriately determined from the viewpoint of the conductivity of the conductive resin composition. The total amount of the conductive powder, the lead-free solder powder, the polyvinyl butyral resin and the organic acid compound in the conductive resin composition is taken as 100 mass%, and the content is, for example, 5.0 mass% or more, preferably 60.0 mass% or more, more preferably 85.0 mass% or more, and even more preferably 90.0 mass% or more, for example, 97.0 mass% or less.
[0026] <Lead-free solder powder> In the conductive resin composition of the present invention, a lead-free solder powder that does not contain lead is used in consideration of the effects on workers, users, the environment, etc. There are no particular limitations on the lead-free solder powder, so long as it does not contain more than the amount of lead that is unavoidably contained.
[0027] The melting point of the lead-free solder powder is preferably 300° C. or less, more preferably 220° C. or less, and even more preferably 50° C. or more and 220° C. or less. If the melting point of the lead-free solder powder exceeds 300° C., the connected members such as circuit boards and electronic components may be thermally destroyed or thermally deteriorated. If the melting point is less than 50° C., the mechanical strength may be weakened, and the reliability of the conductive connection may be reduced.
[0028] Examples of lead-free solder powders include lead-free solder powders based on tin (Sn) and containing one or more elements selected from the group consisting of silver (Ag), bismuth (Bi), zinc (Zn), copper (Cu), indium (In), aluminum (Al), and antimony (Sb) (e.g., Sn-Bi, Sn-Cu, Sn-Sb, Sn-Zn, Sn-Ag, Sn-Ag-Cu, Sn-Zn-Bi, Sn-Ag-In-Bi, Sn-Zn-Al, Sn-Ag-Bi, Sn-Ag-Cu-Bi, Sn-Ag-Cu-Bi-In-Sb, etc.), Bi-based lead-free solder powders (Bi-In, etc.), and In-based lead-free solder powders (In-Ag, In-Bi, etc.).
[0029] The shape of the lead-free solder powder is not particularly limited. Spherical, nearly spherical (for example, with a length-to-width aspect ratio of 1.5 or less), flat, polyhedral, flaky, fibrous, irregular, etc. can be used depending on the application. In the present invention, from the viewpoints of connection stability, volume resistivity, dispersibility, handling, etc., spherical, nearly spherical, flat, or flaky shapes are preferred.
[0030] The volume average particle size of the lead-free solder powder is not particularly limited. D50 can be, for example, 0.5 μm or more, preferably 1.0 μm or more, more preferably 5.0 μm or more, and can be, for example, 50.0 μm or less, preferably 40.0 μm or less, more preferably 30.0 μm or less. If D50 is less than 0.5 μm, the dispersibility and handling of the lead-free solder powder may be reduced. If D50 exceeds 50.0 μm, the connection stability may be reduced, the volume resistivity may be increased, and the dispersibility and handling may be reduced.
[0031] The content of the lead-free solder powder in the conductive resin composition is not particularly limited. It can be appropriately determined from the viewpoint of the conductivity of the conductive resin composition. The total amount of the conductive powder, the lead-free solder powder, the polyvinyl butyral resin and the organic acid compound in the conductive resin composition is taken as 100 mass%, and the content is, for example, 5.0 mass% or more, preferably 10.0 mass% or more, more preferably 20.0 mass% or more, and even more preferably 25.0 mass%, and for example, 85.0 mass% or less, preferably 82.0 mass% or less, and more preferably 80.0 mass% or less.
[0032] <Polyvinyl butyral resin> Polyvinyl butyral resins are resins in which the alcohol portion of polyvinyl alcohol is acetalized with butyraldehyde. They are generally thermoplastic resins that contain vinyl butyral units represented by the following formula (1), vinyl acetate units represented by the following formula (2), and vinyl alcohol units represented by the following formula (3) as main repeating units. [ka]
[0033] The physical properties, chemical properties, mechanical properties, etc. of polyvinyl butyral resins vary depending on the ratio of the units of the above formulas (1) to (3) and the weight average molecular weight (degree of polymerization). For example, by increasing the amount of vinyl butyral units represented by (1) in a polyvinyl butyral resin (increasing the degree of butyralization), compatibility and solubility in non-polar solvents can be improved. By increasing the amount of vinyl acetate units represented by (2) (increasing the amount of acetyl groups), the viscosity when dissolved in a solvent can be reduced, and the glass transition temperature of the resin can be lowered. By increasing the amount of vinyl alcohol units represented by formula (3), adhesion and solubility in polar solvents can be improved.
[0034] In the present invention, the ratio of the butyral group, the acetyl group, and the hydroxyl group in the polyvinyl butyral resin is not particularly limited. For example, the ratio of the butyral group, the acetyl group, and the hydroxyl group may be 55 mol% to 80 mol%, 25 mol% or less, and 10 mol% to 20 mol%, respectively, based on the total amount of these groups being 100 mol. In the present invention, when a nickel-based metal powder is used as the conductive powder, it is preferable that the amount of acetyl groups is large. For example, it is preferable to use a polyvinyl butyral-based resin having an acetyl group amount of 7 mol % or more and 25 mol % or less.
[0035] The weight average molecular weight of the polyvinyl butyral resin is not particularly limited, and may be, for example, 10,000 or more, preferably 20,000 or more, and may be, for example, 250,000 or less, preferably 120,000 or less, from the viewpoint of the mechanical properties of the conductive resin composition and the compatibility with the solvent.
[0036] The polyvinyl butyral resin may be produced by any known method without any limitation, for example, by reacting an aqueous polyvinyl alcohol solution with butyraldehyde in the presence of an acid catalyst, neutralizing the resulting polyvinyl butyral resin slurry with an alkali, separating the resulting mixture from the solvent, washing, dehydrating, and drying to produce a powdered resin.
[0037] The polyvinyl butyral resin may be a commercially available product. For example, S-LEC series (e.g., BL-1, BL-1H, BL-2H, BL-5Z, BL-7Z, BL-10, BL-S, BM-1, BM-2, BM-5, BM-S, BM-SHZ, BH-3, BH-6, BH-A, BH-S, BX-1, BX-L, BX-3, BX-5, KS-1, KS-5Z, KS-6Z, KS- 10, KX-1, KX-5, KW-M, KW-10, SV-12, SV-16, SV-22, SV-26, etc.), and the Mowital series (for example, LPB16B, B20H, 30T, 30H, 30HH, 45M, 45H, 60H, 60T, 60HH, 70HH, 75H, etc.) manufactured by Kuraray Co., Ltd. may be used.
[0038] The content of the polyvinyl butyral resin in the conductive resin composition is not particularly limited. It can be appropriately determined from the viewpoint of the conductivity of the conductive resin composition. The total amount of the conductive powder, the lead-free solder powder, the polyvinyl butyral resin and the organic acid compound in the conductive resin composition is taken as 100 mass%, and the content is, for example, 1.0 mass% or more, preferably 2.0 mass% or more, more preferably 3.0 mass% or more, and for example, 15.0 mass% or less, preferably 12.0 mass% or less, more preferably 10.0 mass% or less.
[0039] <Organic acid compounds> The organic acid compound is, for example, RX n (wherein R is hydrogen or an organic group having 1 to 50 carbon atoms, X is an acid group and multiple Xs may be different from each other, and n is an integer of 1 or more). Examples of the acid group represented by X include a carboxyl group (-COOH), a carboxylic anhydride group (-C(=O)-OC(=O)-), a sulfonic acid group (-SO3H), and a phosphoric acid group (-PO3H2). Examples of the organic acid compound include an organic carboxylic acid compound, an organic carboxylic anhydride, an organic sulfonic acid compound, and an organic phosphonic acid compound. By using an organic acid compound, the dispersibility of the conductive powder is improved and the conductive powder can be efficiently arranged, thereby improving the reliability of the conductive connection and insulation.
[0040] (Organic carboxylic acid compounds) The organic carboxylic acid compound is not particularly limited as long as it is a compound having one or more carboxyl groups (-COOH) in the molecular structure and having 1 to 50 carbon atoms. Examples of organic carboxylic acid compounds include formic acid, acetic acid, propionic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, octylic acid, lauric acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, 12-hydroxystearic acid, ricinoleic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, and monilinic acid. Acid, melissic acid, lactic acid, gluconic acid, malic acid, tartaric acid, succinic acid, maleic acid, fumaric acid, glutaconic acid, benzoic acid, ascorbic acid, glutaric acid, abietic acid, malonic acid, pimelic acid, azelaic acid, dodecanoic acid, eicosanoic acid, citric acid, suberic acid, sebacic acid, caproic acid, enanthic acid, caprylic acid, pelargonic acid, capric acid, arachidonic acid, eicosapentaenoic acid, dodecanoic acid, ole ... Examples of the acidic acid include at least one selected from the group consisting of cosahexaenoic acid, dodecenylsuccinic acid, citraconic acid, mesaconic acid, itaconic acid, dimethylolpropionic acid, dimethylolbutanoic acid, dimethylolbutyric acid, dimethylolvaleric acid, trimethylolpropanoic acid, trimethylolbutanoic acid, salicylic acid, pyruvic acid, paramethylbenzoic acid, toluic acid, 4-ethylbenzoic acid, 4-propylbenzoic acid, 2-methylpropanoic acid, isopentanoic acid, 2-ethylhexanoic acid, acrylic acid, methacrylic acid, propiolic acid, crotonic acid, 2-ethyl-2-butenoic acid, oxalic acid, adipic acid, hexanetricarboxylic acid, cyclohexylcarboxylic acid, 1,4-cyclohexyldicarboxylic acid, ethylenediaminetetraacetic acid, isophthalic acid, terephthalic acid, naphthalenedicarboxylic acid, trimellitic acid, and pyromellitic acid.
[0041] (Organic carboxylic acid anhydride) The organic carboxylic acid anhydride is not particularly limited as long as it is a compound having one or more carboxylic acid anhydride groups (-C(=O)-OC(=O)-) in the molecular structure. The organic carboxylic acid anhydride is obtained by intermolecular dehydration of two organic carboxylic acid molecules and / or intramolecular dehydration of one organic carboxylic acid molecule. In the present invention, for example, among the organic carboxylic acids, one or more selected from the group consisting of those obtained by intermolecular dehydration of an organic monocarboxylic acid and those obtained by molecular dehydration of an organic polycarboxylic acid can be mentioned. In the present invention, preferred examples of the anhydride include one or more selected from the group consisting of acetic anhydride, propionic anhydride, oxalic anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride, succinic anhydride, 2-methylsuccinic anhydride, and the like.
[0042] (Organic sulfonic acid compounds) The organic sulfonic acid compound is not particularly limited as long as it has one or more sulfonic acid groups (-SO3H) in its molecular structure. For example, benzenesulfonic acid, n-butylbenzenesulfonic acid, n-octylbenzenesulfonic acid, n-dodecylbenzenesulfonic acid, pentadecylbenzenesulfonic acid, 2,5-dimethylbenzenesulfonic acid, p-chlorobenzenesulfonic acid, 2,5-dichlorobenzenesulfonic acid, p-phenolsulfonic acid, cumenesulfonic acid, xylenesulfonic acid, o-cresolsulfonic acid, m-cresolsulfonic acid, p-cresolsulfonic acid, p-toluenesulfonic acid, 2-naphthalenesulfonic acid, 1-naphthalenesulfonic acid, styrenesulfonic acid, 4,4-biphenyldisulfonic acid, anthraquinone-2-sulfonic acid, m-benzenedisulfonic acid, a Examples of the sulfonic acid compounds include aromatic sulfonic acid compounds such as diphenylphosphite-2,4-disulfonic acid, anthraquinone-1,5-disulfonic acid, and polystyrene sulfonic acid; aliphatic sulfonic acid compounds such as methanesulfonic acid, ethanesulfonic acid, 1-propanesulfonic acid, n-octylsulfonic acid, pentadecylsulfonic acid, trifluoromethanesulfonic acid, trichloromethanesulfonic acid, 1,2-ethanedisulfonic acid, 1,3-propanedisulfonic acid, aminomethanesulfonic acid, and 2-aminoethanesulfonic acid; and alicyclic sulfonic acid compounds such as cyclopentanesulfonic acid, cyclohexanesulfonic acid, and 3-cyclohexylaminopropanesulfonic acid.
[0043] In the present invention, preferred examples of the sulfonic acid include one or more selected from the group consisting of benzenesulfonic acid, dodecylbenzenesulfonic acid, methanesulfonic acid, p-phenolsulfonic acid, p-toluenesulfonic acid, and (poly)styrenesulfonic acid.
[0044] (Organophosphonic acid compounds) The organic phosphonic acid compound is not particularly limited as long as it has one or more phosphate groups (-PO3H2) in its molecular structure. For example, 1-hydroxyethylidene-1,1-diphosphonic acid, 1-hydroxypropylidene-1,1-diphosphonic acid, 1-hydroxybutylidene-1,1-diphosphonic acid, aminotrimethylenephosphonic acid, methyldiphosphonic acid, nitrotrimethylenephosphonic acid, ethylenediaminetetramethylenephosphonic acid, ethylenediaminebismethylenephosphonic acid, hexamethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, cyclohexanediaminetetramethylenephosphonic acid, and the like. Examples of the acid phosphate include one or more selected from the group consisting of phosphonic acid, carboxyethylphosphonic acid, phosphonoacetic acid, 2-phosphonobutane-1,2,4-tricarboxylic acid, 2,3-dicarboxypropane-1,1-diphosphonic acid, phosphonobutyric acid, phosphonopropionic acid, sulfonylmethylphosphonic acid, N-carboxymethyl-N,N-dimethylenephosphonic acid, N,N-dicarboxymethyl-N-methylenephosphonic acid, 2-ethylhexyl acid phosphate, stearyl acid phosphate, benzenephosphonic acid, and the like.
[0045] The organic phosphonic acid compound may be a surfactant having a phosphate group in its molecular structure. The surfactant having a phosphoric acid group is preferably one having a polyoxyethylene group or a phenyl group in the molecular structure. For example, one or more selected from the group consisting of polyoxyethylene alkylphenyl ether phosphate, polyoxyethylene alkyl ether phosphate, dipolyoxypropylene lauryl ether phosphate, dipolyoxyethylene oleyl ether phosphate, dipolyoxyethylene oxypropylene lauryl ether phosphate, dipolyoxypropylene oleyl ether phosphate, ammonium lauryl phosphate, ammonium octyl ether phosphate, ammonium cetyl ether phosphate, polyoxyethylene lauryl ether phosphate, polyoxyethylene oxypropylene lauryl ether phosphate, polyoxypropylene lauryl ether phosphate, polyoxyethylene tristyryl phenyl ether phosphate, polyoxyethylene oxypropylene tristyryl phenyl ether phosphate, polyoxypropylene tristyryl phenyl ether phosphate, etc. As the surfactant having a phosphate group, one or more types selected from the group consisting of commercially available products such as Phosphanol (trade name) manufactured by Toho Chemical Industry Co., Ltd. and Disperbyk (trade name) manufactured by BYK-Chemie Japan KK can be used.
[0046] (Content) The content of the organic acid compound in the conductive resin composition is not particularly limited. It can be appropriately determined from the viewpoint of the conductivity and stability of the conductive resin composition. The total amount of the conductive powder, the lead-free solder powder, the polyvinyl butyral resin and the organic acid compound in the conductive resin composition is taken as 100 mass%, and the content is, for example, 0.1 mass% or more, preferably 0.5 mass% or more, and, for example, 10.0 mass% or less, preferably 8.0 mass% or less, more preferably 7.0 mass% or less, and even more preferably 4.0 mass% or less.
[0047] <Other ingredients> The conductive resin composition of the present invention may be mixed with one or more additives selected from the group consisting of solvents, resins other than polyvinyl butyral-based resins, pigments, fillers, antioxidants, corrosion inhibitors, defoamers, dispersants, viscosity adjusters (thixotropy adjusters), adhesion promoters, coupling agents, anti-settling agents, leveling agents, and the like, as necessary.
[0048] (solvent) The conductive resin composition of the present invention may contain a solvent. This can improve the fluidity of the conductive resin composition and contribute to improving workability. In addition, by mixing the conductive resin composition with a solvent, a conductive resin paste, a conductive ink, or a circuit connecting agent can be formed.
[0049] As the solvent, any one or more selected from the group consisting of water and various organic solvents can be used. Examples of the organic solvent include alcohols such as ethyl alcohol, propyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, heptyl alcohol, octyl alcohol, nonyl alcohol, decyl alcohol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, methyl methoxybutanol, α-terpineol, β-terpineol, hexylene glycol, benzyl alcohol, 2-phenylethyl alcohol, isopalmityl alcohol, isostearyl alcohol, lauryl alcohol, ethylene glycol, propylene glycol, or glycerin; acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, diacetone alcohol (4-hydroxy-4-methyl-2-pentanone), 2-octyl alcohol, ethyl ketone ... Ketone solvents such as isophorone (3,5,5-trimethyl-2-cyclohexen-1-one) or diisobutyl ketone (2,6-dimethyl-4-heptanone); ester solvents such as ethyl acetate, butyl acetate, diethyl phthalate, dibutyl phthalate, acetoxyethane, methyl butyrate, methyl hexanoate, methyl octanoate, methyl decanoate, methyl cellosolve acetate, ethylene glycol monobutyl ether acetate, propylene glycol monomethyl ether acetate, 1,2-diacetoxyethane; Ether solvents such as dihydrofuran, dimethyl ether, diethyl ether, dipropyl ether, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol dibutyl ether, propylene glycol dimethyl ether, ethoxyethyl ether, 1,2-bis(2-diethoxy)ethane or 1,2-bis(2-methoxyethoxy)ethane; ester ethers such as 2-(2-butoxyethoxy)ethane acetate; ether alcohol solvents such as 2-(2-methoxyethoxy)ethanol;Examples of the solvent include at least one selected from the group consisting of hydrocarbon solvents such as benzene, toluene, xylene, n-paraffin, isoparaffin, dodecylbenzene, turpentine oil, kerosene, and light oil; nitrile solvents such as acetonitrile and propionitrile; nitrogen-containing polar solvents such as dimethylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone; and silicone oil solvents.
[0050] When a solvent is used, the amount of the solvent used is not particularly limited, and may be appropriately adjusted so that the viscosity of the conductive resin composition is such that the composition can be appropriately applied, printed, etc. onto a substrate and / or can be appropriately impregnated into a porous body.
[0051] (Resins other than polyvinyl butyral resins) The conductive resin composition of the present invention may contain a resin other than the polyvinyl butyral-based resin. The resin other than the polyvinyl butyral-based resin may be either a thermosetting resin or a thermoplastic resin, and one or more kinds of the resin may be used. The thermosetting resin may be, for example, one or more resins selected from the group consisting of epoxy resins, phenol resins, polyimide resins, polyurethane resins, melamine resins, urea resins, and the like. Examples of the thermoplastic resin include one or more resins selected from the group consisting of polyolefin resins, polyester resins, poly(meth)acrylic resins, phenoxy resins, thermoplastic polyurethane resins, polyamide resins, polycarbonate resins, polyphenylene ether resins, polyvinyl ether resins, polyvinyl alcohol resins, polyvinyl acetate resins, ionomer resins, and the like.
[0052] When a resin other than a polyvinyl butyral-based resin is used, the amount used is not particularly limited, and may be appropriately adjusted depending on the usage mode and required properties of the conductive resin composition.
[0053] <Properties of the conductive resin composition> The conductive resin composition of the present invention may be in any form, such as a powder, solid, paste, liquid (varnish), etc. When used as a conductive ink or circuit connecting material, it is preferable that the composition is in a paste or liquid (varnish) form at room temperature (20° C.).
[0054] <Characteristics of the conductive resin composition> The conductive resin composition of the present invention has excellent conductivity. The conductive resin composition has a volume resistivity of 1.0×10 when the conductive film obtained by casting or applying the conductive resin composition onto a peelable substrate, drying the composition, and peeling it off is 1.0×10 -2 The volume resistivity of the conductive film is preferably less than 8.0×10 -3 Less than Ω cm, preferably 7.5×10 -3 The volume resistivity is less than Ω·cm. Here, the volume resistivity is obtained by the method described in the examples. The conductive resin composition of the present invention has excellent adhesion to various substrates. The adhesion to glass or PET is evaluated by the method described in the Examples. Furthermore, the conductive resin composition of the present invention has excellent storage stability: no change in viscosity, such as thickening, occurs before and after two months of storage, and no precipitation or separation occurs.
[0055] <Method for preparing conductive resin composition> In preparing the conductive resin composition of the present invention, the conductive powder, the lead-free solder powder, the polyvinyl butyral resin, and the organic acid compound are essential components, and additive components such as a solvent, if necessary, can be added to a mixing vessel in any order and mixed to produce the conductive resin composition. For example, a method of mixing using a ball mill, a roll mill, a bead mill, a planetary mixer, a tumbler, a stirrer, an agitator, a mechanical homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, a paint shaker, a V-type blender, a Nauta mixer, a Banbury mixer, a kneading roll, or a single-screw or twin-screw extruder is appropriately used.
[0056] The temperature during preparation of the conductive resin composition (the temperature during mixing of the components) is not particularly limited. If necessary, heating or the like can be performed, and the temperature can be, for example, 10°C or higher and 100°C or lower. The atmosphere in which the conductive resin composition is prepared is not particularly limited, and the preparation can be performed in air or in an inert atmosphere.
[0057] <Applications of the conductive resin composition> The conductive resin composition of the present invention can be used to manufacture a conductive object. The conductive object may contain other members in addition to the conductive resin composition. Examples of the conductive object include one or more selected from the group consisting of conductive ink, circuit connection material, conductive paste, conductive film, conductive fiber, conductive paint, conductive material for semiconductor packages, conductive material for microelectronic devices, antistatic material, electromagnetic wave shielding material, anisotropic conductive adhesive (die attachment adhesive, etc.), die attach paste, actuator, sensor, conductive resin molded body, etc. The conductive liquid composition is used for imparting, etc.
[0058] For example, by using a solvent as a component of a conductive resin composition, it is possible to prepare a conductive ink, a conductive paste, a conductive paint, etc. The viscosity of the conductive resin composition is not particularly limited, and the conductive resin composition can be in the form of a low-viscosity varnish to a high-viscosity paste, etc., depending on the application. For example, a conductive resin composition, optionally including a solvent, can be applied to various substrates by casting, dipping, bar coating, dispenser, roll coating, gravure coating, screen printing, flexographic printing, spray coating, spin coating, inkjet, or the like, and then dried by heating at a temperature of 300° C. or less to form a conductive film. The atmosphere during drying can be one or more selected from the group consisting of air, inert gas, vacuum, reduced pressure, and the like. In particular, from the viewpoint of suppressing deterioration of the conductive film (preventing oxidation of the conductive powder, etc.), an inert gas atmosphere such as nitrogen or argon is preferred.
[0059] The conductive resin composition of the present invention can be molded by a molding method such as extrusion molding, injection molding, compression molding, etc., and used as a molded article. Examples of the molded article include electronic device parts, automobile parts, machine mechanism parts, food containers, films, sheets, fibers, etc.
[0060] [Conductive ink] The conductive ink of the present invention can be obtained by dissolving and / or dispersing the conductive resin composition in a solvent. The conductive ink of the present invention contains, for example, lead-free solder particles, a polyvinyl butyral resin, an organic acid compound and a solvent, and optionally contains additives such as a surfactant, a pH adjuster (amine compound), a leveling agent, a pigment, an ultraviolet absorber, an antioxidant and a flame retardant. The conductive ink can be obtained by placing the above-mentioned components in a mixing container, mixing them using one or more mixers selected from the group consisting of a ball mill, a roll mill, a bead mill, a centrifugal mixer, a planetary mixer, a tumbler, a stirrer, an agitator, a mechanical homogenizer, an ultrasonic homogenizer, a high-pressure homogenizer, a paint shaker, and the like, to form a varnish or paste.
[0061] The conductive ink of the present invention can be used, for example, as a conductive ink for printing to form wiring. The printing method can be, for example, one or more methods selected from the group consisting of screen printing, inkjet printing, flexographic printing, gravure printing, etc. In the present invention, it is preferable to use one or more printing methods selected from the group consisting of screen printing, inkjet printing, etc., because they have excellent printability and shape retention. Here, the mesh used in the screen printing method can be appropriately selected, and it is preferable to employ a mesh that does not remove excessive amounts of the conductive powder in the conductive ink or the lead-free solder powder.
[0062] The thickness of the coating film formed by applying the conductive ink of the present invention can be appropriately adjusted depending on various applications, for example, 1 μm or more, preferably 2 μm or more, more preferably 5 μm or more and 100 μm or less. The conductive ink of the present invention is excellent in one or more properties selected from the group consisting of electrical conductivity, adhesion to various substrates, storage stability, leveling (surface smoothness), printability, and the like.
[0063] [Circuit connecting materials] The circuit connecting material of the present invention is used for conductive connections between various electronic components and circuit boards and for connecting (bonding) electric and electronic circuits to each other. The shape of the circuit connecting material is not particularly limited, but it is preferably in the form of a liquid or film. The liquid circuit connecting material can be obtained, for example, by mixing the conductive resin composition of the present invention with a solvent such as an organic solvent to liquefy it. A film-like circuit connecting material can be obtained, for example, by directly casting and applying the liquefied conductive resin composition of the present invention onto a release substrate to form a film, drying the composition to remove the solvent, forming a film, and then peeling the film off from the release substrate. Furthermore, a film-like circuit connecting material can be obtained, for example, by impregnating a nonwoven fabric or the like with the liquefied conductive resin composition of the present invention, forming the same on a release substrate, drying to remove the solvent, and then peeling the same off from the release substrate.
[0064] There is no particular limitation on the electrical connection method using the circuit connecting material of the present invention. For example, a circuit connecting material is provided between an electrode of an electronic component or circuit and an electrode on a substrate facing the electrode, and heated to electrically connect and bond the electrodes. Pressure can be applied as necessary during heating. The method for providing the circuit connecting material between the opposing electrodes is not particularly limited, and examples thereof include a method of applying a liquid circuit connecting material, a method of sandwiching a film-like circuit connecting material, and the like. In addition, when electrically connecting a pin of an electronic component or the like to a circuit, a method of providing a circuit connection material at the base of the pin and butt-jointing the pin to form an electrically conductive connection can be mentioned.
[0065] The circuit connecting material of the present invention can be used substantially as an anisotropic conductive material, and can also be used in a method for connecting electrodes in which the circuit connecting material having excellent adhesiveness is formed between electrodes facing each other on a substrate, and the electrodes are brought into contact with each other and the substrates are bonded together by heating and pressurization. Substrates for forming electrodes can include inorganic materials such as semiconductors, glass, and ceramics, organic materials such as polyimide and polycarbonate, and composite combinations of these materials such as glass / epoxy. Furthermore, since the circuit connecting material of the present invention contains solder powder that melts at low temperatures, it is possible to achieve conductive connection at low temperatures of 250° C. or less, for example 200° C. or less. EXAMPLES
[0066] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples. Unless otherwise specified, "%" means "% by mass" and "parts" means parts by mass.
[0067] The lead-free solder powder and polyvinyl butyral resin used in the examples and comparative examples are as follows. <Lead-free solder powder> Lead-free solder powder 1: Sn42-Bi58 (type 3) (manufactured by Mitsui Mining & Smelting Co., Ltd., melting point 139°C) Lead-free solder powder 2: Sn42-Bi58 (type 4) (manufactured by Mitsui Mining & Smelting Co., Ltd., melting point 139°C) Lead-free solder powder 3: Sn42-Bi58 (type 5) (manufactured by Mitsui Mining & Smelting Co., Ltd., melting point 139°C) Lead-free solder powder 4: Sn42-Bi58 (ST-3) (manufactured by Mitsui Mining & Smelting Co., Ltd., melting point 139°C)
[0068] <Polyvinyl butyral resin> Resin 1: Polyvinyl butyral resin (Sekisui Chemical Co., Ltd., S-LEC BH-A) Resin 2: Polyvinyl butyral resin (Sekisui Chemical Co., Ltd., S-LEC SV-12) Resin 3: Polyvinyl butyral resin (Sekisui Chemical Co., Ltd., S-LEC SV-16) Resin 4: Polyvinyl butyral resin (Sekisui Chemical Co., Ltd., S-LEC SV-22) Resin 5: Polyvinyl butyral resin (Sekisui Chemical Co., Ltd., S-LEC SV-26)
[0069] In the examples and comparative examples, the characteristics (electrical conductivity and adhesion) of the conductive resin composition were measured and evaluated by the methods described below. <Adhesion> The conductive resin composition was applied onto a glass plate or a PET film (polyethylene terephthalate resin film) to prepare a film having a thickness of 100 μm. The obtained film was cut into six lattice patterns at 2 mm intervals reaching down to the substrate according to the cross-cut method of JIS K 5600, and then cellophane tape (registered trademark) was applied and peeled off to evaluate adhesion based on the degree to which the film peeled off. A: No peeling of the film C: The film is peeling off.
[0070] <Conductivity> A film of the conductive resin composition was produced using a spin coater. The volume resistivity of the film was measured using a resistivity meter (Loresta GP-MCP T610, manufactured by Nitto Seiko Analytech Co., Ltd.). In the present invention, the volume resistivity of the conductive film is 1.0×10 -2 Those with a resistance of less than Ω·cm were deemed to have passed.
[0071] <Storage stability> Each sample of the Examples and Comparative Examples was stored in a sealed metal can at room temperature (23±2°C) for two months, and the viscosity was measured using a viscometer (Brookfield, HBDV2). The viscosity change rate was calculated using the following formula (1), and evaluated according to the following evaluation criteria. Viscosity change rate = ((viscosity after static storage - viscosity before storage) / viscosity before storage) × 100 (1) A: Viscosity change rate is within ±10% B: Viscosity change rate is between ±10% and ±20% C: Viscosity change rate is ±20% or more, or precipitation or separation is observed.
[0072] [Example 1] A conductive resin composition was prepared by mixing and stirring 31.8 parts of nickel powder (HCA-1, manufactured by Novamet), 61.6 parts of lead-free solder powder 2, 4.5 parts of resin 1, and 2.1 parts of glutaric acid. The obtained conductive resin composition was dispersed in ethyl diglycol acetate to prepare a conductive resin composition dispersion, which was then applied onto a substrate to prepare a conductive film, and the conductivity, adhesion and storage stability of the film were evaluated. The results are shown in Table 1.
[0073] [Examples 2 to 20, Comparative Examples 1 to 6] Conductive resin compositions were prepared in the same manner as in Example 1, except that the components of the conductive resin compositions and the amounts used were as shown in Tables 1 to 3, and the conductivity, adhesion, and storage stability were evaluated in the same manner as in Example 1. The results are also shown in Tables 1 to 3. The silver powder used in Examples 18 to 20 was flake silver powder AgC-A manufactured by Fukuda Metal Foil and Powder Co., Ltd.
[0074] [Table 1]
[0075] [Table 2]
[0076] [Table 3]
[0077] All of the conductive resin compositions according to Examples 1 to 20 were subjected to a storage stability test (each sample was stored in a sealed metal can at room temperature (23±2°C) for two months), and it was confirmed that they had good fluidity without causing precipitation or separation or thickening, and thus had excellent storage stability.
[0078] As can be seen from Tables 1 to 3, the conductive resin compositions according to Examples 1 to 20 are excellent in conductivity, adhesion and storage stability. The conductive resin composition of Comparative Example 1, which did not contain nickel-based metal powder or silver-based metal powder, had a conductive film with a volume resistivity that was impossible to measure and had extremely poor conductivity. The conductive resin compositions of Comparative Examples 2 to 6, which do not contain an organic acid compound, have a volume resistivity of 3.9 × 10 -2 The electrical conductivity was poor, being over Ω·cm.
Claims
1. one or more conductive powders selected from the group consisting of nickel-based metal powder, silver-based metal powder, copper-based metal powder, zinc-based metal powder, aluminum-based metal powder, iron-based metal powder, and gold-based metal powder; Lead-free solder powder, A polyvinyl butyral resin, an organic carboxylic acid compound having two carboxyl groups (-COOH) or an anhydride thereof; Including, the content of the lead-free solder powder is 60.6% by mass or more and 85% by mass or less, based on 100% by mass of the total amount of the conductive powder, the lead-free solder powder, the polyvinyl butyral resin, and the organic carboxylic acid compound or its anhydride in the conductive resin composition; A conductive resin composition having a conductive film having a volume resistivity of less than 1.0×10 −2 Ω·cm.
2. A conductive ink comprising the conductive resin composition according to claim 1.
3. A circuit connecting material comprising the conductive resin composition according to claim 1.
Citation Information
Patent Citations
Connection member of circuit
JP1989059786A
Conductive paste and mounted board using same
JP1993020920A
Conductive composition for solderable electrode of surface heating element
JP1997194668A
Bonding material
JP2003305588A
Anisotropic conductive film
JP2010102859A